Pengaruh Ukuran Siung dan Jarak Tanam terhadap Pertumbuhan dan Hasil Bawang Putih Varietas Lumbu Hijau - Agnofi Merdeka Efendi; Indrawan Fahmi; Samanhudi Samanhudi; Edi Purwanto (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
The effort to increase garlic productivity through improvement of cultivation technology. This study aimed to determine the proper size of cloves and planting distance thus resulting in the best growth and yield of garlic var. Lumbu Hijau. This study was conducted in April-September 2018 in Horticulture Seed Garden Tawangmangu, Karanganyar. This method used was Randomized Complete Block Design (RCBD) factorial with 2 factors, namely clove size (large, medium, and small) and planting distance (10 cm x 10 cm, 12.5 cm x 12.5 cm, 10 cm x 15 cm). The result showed that the size of cloves had significant effect on plant height, number of leaves, plant dry weight and yield. Planting distance had significant effect on yield. The use of large sized cloves (diameter 19-35 mm) increased plant height, number of leaves, plant dry weight and yield of garlic var. Lumbu Hijau. Maximum garlic yields on spacing of 10 cm x 10 cm. The combination of the size of the cloves with spacing affected plant height, plant weight and the yield of garlic. The greater the size of the cloves with the wider planting distance causing higher plants. The smaller the size of the cloves with a wider spacing causing low garlic yield.